2021
DOI: 10.2106/jbjs.20.01144
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported and Radiographic Outcomes of Joint-Preserving Surgery for Rheumatoid Forefoot Deformities

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune disorder and a chronic inflammatory disease that can damage joints throughout the body. As dramatic improvements in medical treatment have contributed to reduced progression of joint destruction, surgical methods for the treatment of RA-related forefoot deformities have gradually changed from joint-sacrificing to joint-preserving. The aim of this study was to assess the long-term outcomes, including patient-reported outcomes, of joint-preservin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 54 publications
1
22
1
2
Order By: Relevance
“…In the present study, the recurrence rate of HV deformities was 13.9%, which was not worse compared with that reported in previous studies on joint-preserving surgery in patients with RA (0-40%) [11,[13][14][15][16]37,38]. Reported risk factors for recurrent HV after joint-preserving procedures in patients with RA include severe preoperative deformity, high preoperative RA disease activity, splayfoot, and hindfoot malalignment [13,15,39,40].…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In the present study, the recurrence rate of HV deformities was 13.9%, which was not worse compared with that reported in previous studies on joint-preserving surgery in patients with RA (0-40%) [11,[13][14][15][16]37,38]. Reported risk factors for recurrent HV after joint-preserving procedures in patients with RA include severe preoperative deformity, high preoperative RA disease activity, splayfoot, and hindfoot malalignment [13,15,39,40].…”
Section: Discussionsupporting
confidence: 47%
“…In a retrospective study of 35 feet, Ebina et al reported that joint-preserving arthroplasty, including modified scarf osteotomy for the hallux and off-set shortening osteotomy for the lesser toes, significantly improved all SAFE-Q subscale scores [24]. Another retrospective study by Yano et al including 105 feet demonstrated that joint-preserving surgery including proximal rotational closing-wedge osteotomy of the first metatarsal and shortening oblique osteotomies of the lesser toes also significantly improved all SAFE-Q subscale scores [16]. Additionally, Chao et al reported a significant improvement in the Short Form 36 score postoperatively in a retrospective study of 37 feet that were treated with a joint-preserving procedure of the first MTP joint, including Ludloff, scarf, and chevron osteotomies [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as limitations, investigations in longer periods with a more increased number should also be done, because RA is a chronic and progressive disease. However, we believe that the combined surgery is one of the novel surgical procedures for rheumatoid forefoot deformity, as well as other novel combined joint-preserving forefoot surgeries [ 6 , 11 , 12 ] ( Table 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have been choosing the combination surgery of modified scarf osteotomy for the correction of hallux alignment [ 1 , 2 , 3 ] and metatarsal shortening offset osteotomy for the reduction of dislocated/subluxated metatarsophalangeal (MTP) joints in lesser toes [ 2 , 4 ]. These procedures were reported to be useful for the reconstruction of rheumatoid forefoot deformity, as well as other joint-preserving surgical procedures [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In this study, responses to a self-administered foot evaluation questionnaire (SAFE-Q) were also included to evaluate the combination surgery, and risk factors for recurrence of hallux valgus (HV) deformity and lesser toe MTP joint subluxation were also investigated.…”
Section: Introductionmentioning
confidence: 99%